Effect of Re content on microstructure and mechanical properties of TiCN–WC–HfN ceramics - GAO Jiaojiao; PING Ping; LIU Jiabao; SONG Jinpeng (Fenmo yejin jishu)
TiCN–WC–HfN ceramics were prepared by vacuum hot pressing sintering technology, and the effects of Re contents (molar fraction) on the microstructure and mechanical properties of the ceramics were investigated. The results show that, the TiCN–WC–HfN–Ni–Re ceramics are composed of TiC0.41N0.5, WC, HfN, TiC, Ni and Re, and TiC0.4N0.50 is the solid solution formed between TiC and TiN in the sintering process. Micro-pits and cleavage planes are discovered in the fracture surface of TiCN–WC–HfN ceramics with the different molar fraction of Re. When the molar fraction of Re is 2.5%, there are more micro-pits on the ceramic fractures. When the mole fraction of Re increases from 0 to 3.0%, the Vickers hardness, flexural strength, and fracture toughness of the TiCN–WC–HfN ceramics first increase and then decrease. When the mole fraction of Re is 2.5%, the mechanical properties of the ceramics show the best as the Vickers hardness is (19.25±0.21) GPa, bending strength is (1304±23) MPa, and fracture toughness is (7.73±0.22) MPa∙m1/2. Transgranular fracture and intergranular fracture of the TiCN–WC–HfN–Ni–Re ceramics occur during the fracture process, and the toughening mechanisms are the crack deflection and crack bridging.